Refinement of Fertilizer Prescriptions Equations of Bt. Cotton Hybrids under Integrated Plant Nutrient Supply in Semi-Arid Inceptisols of Haryana - V. Goyal (Journal of the Indian Society of Soil Science, 2023)
A field experiment was conducted at Research Farm of CCS Haryana Agricultural University, Hisar during kharif 2018 to refine the pre-existing fertilizer prescription equations of nitrogen (N), phosphorus (P2O5) and potassium (K2O) for Bt. cotton hybrids and its validation was done at different locations of semi-arid regions of Haryana with the aim to balance the use of fertilizers for higher productivity and better soil health during kharif 2019 and 2020. Using the experimental data, the basic parameters viz. nutrient requirement (NR), per cent contribution of nutrients from soil (CS), fertilizers (CF) and farmyard manure (CFYM) towards total nutrient uptake by Bt. cotton were computed based on soil test crop response (STCR) targeted yield approach. The nutrient required to produce one quintal of seed cotton yield was 1.68, 0.8 and 1.18 kg N, P2O5 and K2O, respectively. It was observed that 27.89, 45.21 and 6.24% of N, P2O5 and K2O, respectively were contributed from the soil in achieving the desired yield targets while it was 11.25, 20.79 and 78.73% for N, P2O5 and K2O, respectively from fertilizers. These basic parameters were used in generating the refined fertilizer prescription integrated plant nutrient system (IPNS) based equations for Bt. cotton. Based on these fertilizer prescription equations, the ready reckoners were formulated for desired yield targets of 2.8, 3.0 and 3.2 t ha-1 at varying soil test values of N, P2O5 and K2O, respectively. The ready reckoner of Bt. cotton at different yield targets showed the extent of saving the fertilizers under IPNS as compared to that of general recommended dose of fertilizers (175:60:60 kg ha-1::N:P2O5: K2O). Validation of fertilizer prescription equation of Bt. cotton at different locations of Haryana showed the highest mean seed cotton yield in STCR-IPNS 3.2 which decreased in the following order: STCR-IPNS 3.2 > STCR 3.2 > STCR-IPNS 2.8 > STCR 2.8 > GRD >FP > control. The response to fertilizer application also followed the same trend. The maximum variation of 30.0% was observed under STCR-IPNS 3.2 treatment while an increase of 28.0% in seed cotton yield was observed in STCR 3.2 treatment over the farmer’s practice. The balanced fertilization due to STCR approach resulted an increase in B:C up to 14.40 Rs/Re ranging from 12.49 to 14.40 Rs/Re under different STCR and STCR-IPNS treatments in Bt. cotton. The results clearly revealed that the STCR based fertilizer recommendations for 3.2 t ha-1 yield targets under irrigated conditions in cotton growing area of Haryana proved superior over generalized recommended dose due to higher productivity, response and benefit to farmers.